Groundwater Pumping Management in Controlling Seawater Up-Coning in The North Coastal Area of Makassar - Badaruddin, Sugiarto; Azis, Akhmad; Ashari, Muhammad Fadhil; Jannah, Miftahul; Ali, Ilham; Ihsan, Muhammad (Politeknik Negeri Ujung Pandang, 2020)
In big cities, communities generally consume clean water from local water supply company which uses surface water sources. However, due to the limitations of the company in supplying water, particularly in the dry season, an alternative is required, such as using groundwater without causing over-exploitation. This study aims to determine the optimal rate of groundwater pumping in the coastal aquifer to avoid seawater up coning using SEAWAT V.4 numerical model. The research method was carried out using a GEO-7X GPS device to obtain coordinate's location, land elevation and observation well distance from the coastline. Secondary data in the form of aquifer thickness data and geological map of the site were obtained from previous studies. The salinity test results show that the average salinity value of the ten water samples from observation wells is 36.8 mg/l, which means that the water is categorized as non-saline water (freshwater). These data are in line with the groundwater utilization monitoring activity report of Makassar City Environment Office in 2018, which reported that Ujung Tanah and Wajo Districts were found to be free from seawater intrusion. Even so, the potential for seawater intrusion is still considered high because of the location of community groundwater wells are near from the coast. One of the efforts to prevent seawater up coning is by limiting groundwater pumping. From the numerical modeling results, it is found that the maximum groundwater discharge in the research site, namely P3 is 20% of total flow rate(0.3 m3/day), P5 is 20% (1.32 m3/day), P6 is 40% (0.52 m3/day) and P10 is 20%(0.63 m3/day).